2002
DOI: 10.1067/mcp.2002.121788
|View full text |Cite
|
Sign up to set email alerts
|

Low daily 10‐mg and 20‐mg doses of fluvoxamine inhibit the metabolism of both caffeine (cytochrome P4501A2) and omeprazole (cytochrome P4502C19)

Abstract: No convincing evidence was found that CYP2D6 is an important enzyme for the disposition of fluvoxamine. Other factors seem to be more important. A nontherapeutic oral daily dose of fluvoxamine is sufficient to provide a marked inhibition of both caffeine (CYP1A2) and omeprazole (CYP2C19) metabolism. It was not possible to separate the inhibitory effects of fluvoxamine on these enzymes, even after such a low daily dose such as 10 mg x 1 or x 2 of fluvoxamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…This was in line with previous interaction studies indicating that dose or plasma concentration of fluvoxamine correlated well with the degree of inhibition in the metabolism of various drugs such as clozapine (Markowitz et al 1996;Fabrazzo et al 2000), melatonin (von Bahr et al 2000) and omeprazole (Christensen et al 2002). In addition, we found positive correlations between increase in haloperidol concentra- Drug concentrations (ng/ml) Haloperidol 3.7€4.4 (1.9-6.9) 4.4€1.7 (2.4-7.9)*** 5.2€2.3 (2.5-10.0)** 6.0€3.0 (2.7-12.6)** Reduced haloperidol 1.5€1.7 (0.5-3.1) 1.7€0.9 (0.6-3.8)* 1.9€1.1 (0.8-4.5)* 2.3€1.2 (0.9-4.6)** Fluvoxamine -16.9€9.8 (4.5-37.5) 55.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was in line with previous interaction studies indicating that dose or plasma concentration of fluvoxamine correlated well with the degree of inhibition in the metabolism of various drugs such as clozapine (Markowitz et al 1996;Fabrazzo et al 2000), melatonin (von Bahr et al 2000) and omeprazole (Christensen et al 2002). In addition, we found positive correlations between increase in haloperidol concentra- Drug concentrations (ng/ml) Haloperidol 3.7€4.4 (1.9-6.9) 4.4€1.7 (2.4-7.9)*** 5.2€2.3 (2.5-10.0)** 6.0€3.0 (2.7-12.6)** Reduced haloperidol 1.5€1.7 (0.5-3.1) 1.7€0.9 (0.6-3.8)* 1.9€1.1 (0.8-4.5)* 2.3€1.2 (0.9-4.6)** Fluvoxamine -16.9€9.8 (4.5-37.5) 55.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we found positive correlations between increase in haloperidol concentra- Drug concentrations (ng/ml) Haloperidol 3.7€4.4 (1.9-6.9) 4.4€1.7 (2.4-7.9)*** 5.2€2.3 (2.5-10.0)** 6.0€3.0 (2.7-12.6)** Reduced haloperidol 1.5€1.7 (0.5-3.1) 1.7€0.9 (0.6-3.8)* 1.9€1.1 (0.8-4.5)* 2.3€1.2 (0.9-4.6)** Fluvoxamine -16.9€9.8 (4.5-37.5) 55. 2€27.8 (15.4-110) 139 Fluvoxamine is known as not only a potent inhibitor of CYP1A2 and CYP2C19 (Christensen et al 2002), but also a moderate inhibitor of CYP3A4, based on in vivo (Fleishaker et al 1994) and in vitro (von Moltke et al 1995) interaction studies between fluvoxamine and alprazolam, which is a specific substrate of CYP3A4 (Yasui et al 1996). In a previous study, we found that itraconazole, a potent inhibitor of CYP3A4, elevated haloperidol concentration, indicating the involvement of CYP3A4 in the metabolism of haloperidol (Yasui et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Fluvoxamine is metabolized in part by CYP2D6 and to a lesser extent by CYP1A2 ). Data are PHARMACOGENETICS, DRUG METABOLISM, AND CLINICAL PRACTICE conflicting regarding the effect of CYP2D6 on fluvoxamine concentrations, with a single-dose study reporting a 1.3-fold higher AUC in PMs , whereas in another no difference was observed (Christensen et al, 2002). Similar disparities were observed at steady state (Spigset et al, 1998;Christensen et al, 2002).…”
Section: Doxepin (Tertiary)/desmethyldoxepin (Secondary)mentioning
confidence: 51%
“…[36][37][38] Enzyme inhibition by the substrate itself was described to convert genotypic extensive metabolizers of CYP2D6 substrates to phenotypically poor metabolizers in antidepressant drug therapy. [39][40][41] Drug target polymorphisms Data analysis We included all available studies concerning response to therapy and adverse drug reactions. We did not include studies on genetic polymorphisms as risk factors for the genetic susceptibility to mental illness.…”
Section: Metabolic Polymorphismsmentioning
confidence: 99%